Implementation Kinematics Modeling and Odometry of Four Omni Wheel Mobile Robot on The Trajectory Planning and Motion Control Based Microcontroller - Dhiya Uddin Rijalusalam; Iswanto Iswanto (Journal of Robotics and Control (JRC), 2021)
The control of kinematic modeling in a four wheel omni-directional robot (FWOR) is very difficult. Because you have to adjust the speed of the four DC motors. The speed of DC motors is controlled so that the FWOR robot can be controlled. This paper will explain the application of kinematic modeling of four wheel omni directional robots as track tracking controllers and microcontroller based movement control. Kinematic is the study of robot motion based on geometric structure analysis of a stationary / moving reference coordinate frame system without considering the force, torque or certain moments that cause movement. By applying kinematic modeling and calculation of the odometric system as feedback, the control of the robot trajectory movement can be controlled with precision in accordance with the path planning that has been made. The robot track control technique is embedded in a 32-bit ARM microcontroller. The path planning system and observing robot movement are carried out using a friendly graphic interface using Processing to facilitate the robot monitoring process. The results of the experiments and tests carried out, the system is able to control the rate of movement of the robot with great precision in accordance with the path planning made.